Pengembangan Lampu Jalan Umum Dengan Listrik Tenaga Surya Di Desa Cilatak Kecamatan Ciomas Kabupaten Serang Banten - ANDI MAKKULAU; Kartika Tresya Mauriraya; Rio Afrianda; Nurmiati Pasra (Sekolah Tinggi Teknik - PLN, 2021)
Photovoltaic systems or solar power plants convert electromagnetic energy from sunlight into electrical energy. This renewable energy based power plant is one of the recommended solutions for electricity in remote rural areas where sunlight is abundant and fuel is difficult to obtain and relatively expensive. The Ministry of Energy and Mineral Resources has issued Ministerial Regulation regarding the use of the Roof Solar Power Plant system by consumers of the Indonesian Electricity Company (PLN). It is hoped that with this regulation the solar panel business and industry can flourish. The method we use in this Community Service is the observation method. By making observations in the field accompanied by interviews with the surrounding population becomes our primary data source in determining the needs of the problems that occur. In Cilatak Village we found minimal of street lighting, and limited electricity supply, for this reason we strongly support programs for new and renewable energy for remote areas that are difficult to get electricity supply. Based on this, we created the Development of Public Street Lights with Solar Electricity in Cilatak Village, Ciomas District, Serang District, Banten, so that the problems of public road lighting can be overcome, and we educated the utilization and maintenance.